Synthesis of Arylpalladium(II) Boronates: Confirming the Structure and Chemical Competence of Pre‐transmetalation Intermediates in the Suzuki–Miyaura Reaction. (26th May 2021) - Olding, Angus; Ho, Curtis C.; Canty, Allan J.; Lucas, Nigel T.; Horne, James; Bissember, Alex C.
Abstract: Palladium(II) boronates are recognized as fundamental pre‐transmetalation intermediates in Suzuki–Miyaura cross‐couplings. While these typically transient species have been detected and studied spectroscopically, it is conspicuous that they have never been isolated since this important reaction was discovered over forty years ago. This study reports the synthesis of a family of unprecedented arylpalladium(II) boronates that are, by design, kinetically stable at ambient temperature, both in solution and in the solid state. These properties enabled unambiguous crystallographic confirmation of their structure for the first time and their chemical competence in a Suzuki–Miyaura reaction was demonstrated. Abstract : Palladium(II) boronates are fundamental pre‐transmetalation intermediates in the Suzuki–Miyaura reaction that are typically transient and have never been isolated. Arylpalladium(II) boronates have now been synthesized that are kinetically stable in solution, which enabled their isolation and crystallographic characterization. These species were shown to be chemically competent in Suzuki–Miyaura couplings.